Targeted Ablation of Periostin-Expressing Activated Fibroblasts Prevents Adverse Cardiac Remodeling in Mice. Issue 12 (10th June 2016) - Kaur, Harmandeep; Takefuji, Mikito; Ngai, C.Y.; Carvalho, Jorge; Bayer, Julia; Wietelmann, Astrid; Poetsch, Ansgar; Hoelper, Soraya; Conway, Simon J.; Möllmann, Helge; Looso, Mario; Troidl, Christian; et al.
Abstract : Rationale: : Activated cardiac fibroblasts (CF) are crucial players in the cardiac damage response; excess fibrosis, however, may result in myocardial stiffening and heart failure development. Inhibition of activated CF has been suggested as a therapeutic strategy in cardiac disease, but whether this truly improves cardiac function is unclear. Objective: : To study the effect of CF ablation on cardiac remodeling. Methods and Results: : We characterized subgroups of murine CF by single-cell expression analysis and identified periostin as the marker showing the highest correlation to an activated CF phenotype. We generated bacterial artificial chromosome–transgenic mice allowing tamoxifen-inducible Cre expression in periostin-positive cells as well as their diphtheria toxin-mediated ablation. In the healthy heart, periostin expression was restricted to valvular fibroblasts; ablation of this population did not affect cardiac function. After chronic angiotensin II exposure, ablation of activated CF resulted in significantly reduced cardiac fibrosis and improved cardiac function. After myocardial infarction, ablation of periostin-expressing CF resulted in reduced fibrosis without compromising scar stability, and cardiac function was significantly improved. Single-cell transcriptional analysis revealed reduced CF activation but increased expression of prohypertrophic factors in cardiac macrophages and cardiomyocytes, resulting in localized cardiomyocyte hypertrophy. Conclusions: : Modulation of the activated CF population is a promising approach to prevent adverse cardiac remodeling in response to angiotensin II and after myocardial infarction. Abstract : Supplemental Digital Content is available in the text.